Pelagic amphipods (Crustacea: Amphipoda: Hyperiidea) in western Mexico. 2. Family Eupronoidae - Gasca, Rebeca; Hendrickx, Michel E. (Zootaxa, 2021)
During deep-water (0–1550m) sampling operations off western Mexico performed between 1989 and 2014, a series of 89 specimens of pelagic amphipods of the family Eupronoidae was obtained, including two genera and four species: Eupronoe armata, E. maculata, E. minuta, and Parapronoe parva. The most abundant species (50% of total number of individuals) and frequently collected species (in 65% of samples with eupronoids) was E. maculata. Worldwide and regional distributions are provided for each species. Notes on previously used names are provided.